Sistem Pendukung Keputusan Dalam Perangkingan Bedak Terbaik Menerapkan Metode MOORA - Friska Irma Yanti; Rani Patricia Manalu; Mesran Mesran (TIN: Terapan Informatika Nusantara, 2023)
Powder is a makeup product that is owned by every woman who wants to look beautiful. This powder is easy to find in the market and the price varies, from cheap to expensive. Powder has a very important function, which is to make facial skin look healthier, prettier, fresher, even to hide imperfections such as acne scars or black spots which often reduce the perfection of the face. In choosing powder, consumers are often confused about choosing and determining which powder is good and suitable for use. Because of these problems, it is necessary to design a decision support system that can help make a decision in obtaining information in recommending powder. There are several methods provided by SPK including MOORA, WASPAS, MOOSRA, SAW, TOPSIS, WP, SMART, OCRA, ROC, AHP, PSI and others. The method used in this study is the MOORA method. The selection of the best powder is based on the use of criteria which will become predetermined rules for evaluating powder which will be used as an alternative research. Based on the calculation of the MOORA method for 6 alternatives, A2 was obtained as the first rank, followed by A3 and A4